Sprint mechanical properties in soccer players according to playing standard, position, age and sex - Haugen, T. A.; Breitschädel, F.; Seiler, S. (Journal of Sports Sciences, 2020)
The purpose of this study was to quantify possible differences in sprint mechanical outputs in soccer according to soccer playing standard, position, age and sex. Sprint tests of 674 male and female players were analysed. Theoretical maximal velocity (v0), horizontal force (F0), horizontal power (Pmax), force-velocity slope (SFV), ratio of force (RFmax) and index of force application technique (DRF) were calculated from anthropometric and spatiotemporal data using an inverse dynamic approach applied to the centre-of-mass movement. Players of higher standard exhibited superior F0, v0, Pmax, RFmax and DRF scores (small to large effects) than those of lower standard. Forwards displayed clearly superior values for most outputs, ahead of defenders, midfielders and goalkeepers, respectively. Male >28 y players achieved poorer v0, Pmax and RFmax than <20, 20-24 and 24-28 y players (small to moderate), while female <20 y players showed poorer values than 20-24 and >24 y players for the same measures (small). The sex differences in sprint mechanical properties ranged from small to very large. These results provide a holistic picture of the force-velocity-power profile continuum in sprinting soccer players and serve as useful background information for practitioners when diagnosing individual players and prescribing training programmes.